A 3D numerical study on tsunamis ascending a river. Issue 2 (3rd April 2022) - Kakinuma, Taro; Kusuhara, Yoshimi
ABSTRACT: Three-dimensional numerical simulations were generated for tsunamis ascending processes with different river topographies. As tsunamis propagated in a narrow river, the radius of curvature around the first wave peak decreased, increasing the tsunami height with wave disintegration until the second tsunami height peak appeared. The diffracted waves also entered the river channel, causing an increase in tsunami height in the vicinity of the riverbank at the estuary. The tsunami height increased in a uniform riverbed gradient and narrower river width toward the upstream, based on the shallowing and energy concentration. As the angle between the riverbank line and coastline at the estuary was acute, the tsunami height was reduced because the diffracted waves were difficult to enter the river. The tsunami height in the rivers increased as the ratio of representative wavelength to river width was increased. The maximum tsunami height in the bore-shaped wave was larger than in the solitary wave with the same incident wave height. In the case of tsunami propagation in the compound cross-section river, multiple crestlines appeared because the tsunamis traveling diagonally in the flood channel showed multiple reflections both on the riverbank and between the flood and main channels.